Influence of cutting parameters on burr morphology in milling of 1–2 mm SS304 plates - Vian Rizanda Putra; Muhammad Akhlis Rizza (Politeknik Negeri Lhokseumawe, 2026)
Machining SS 304 in thin-plate applications presents a significant challenge due to burr formation arising from its high ductility and pronounced plastic deformation during milling. Within the 1 to 2 mm thickness range, reduced structural rigidity increases the tendency for lateral plastic flow and edge deformation, thereby compromising surface quality and increasing the need for secondary deburring operations. Although burr formation in stainless steel has been widely investigated, studies specifically addressing the influence of conventional milling parameters on burr morphology in thin SS 304 plates remain limited. This study aims to analyse the effects of spindle speeds (400 rpm and 800 rpm) and depth of cut (0.25 mm and 0.5 mm) on burr morphology in SS 304 plates with thicknesses of 1 mm, 1.5 mm, and 2 mm. Macroscopic observations were conducted using an optical microscope equipped with a 5× macro lens to evaluate burr height and deformation characteristics. The results demonstrate that increasing depth of cut consistently leads to higher burr formation due to intensified plastic deformation at the tool exit zone. Spindle speed contributes through thermomechanical effects that influence deformation stability, particularly in plates with differing rigidity. The 1 mm plate exhibited the highest burr value, reaching 284 µm, whereas the 2 mm plate showed more stable deformation behaviour with lower burr heights. These findings indicate that a combination of 800 rpm spindle speed and 0.25 mm depth of cut provides a more controlled burr condition, offering practical guidance for minimising burr defects in the conventional milling of thin SS 304 plates.